Seroprevalence of canine leishmaniasis in Kwara, Oyo and Ogun states of Nigeria (2014)
Leishmaniasis is an important tropical disease that is gradually gaining attention in Nigeria. The canine species which include domestic dogs have been named the reservoir host for the zoonotic form of leishmaniasis. The present study was carried out to determine the seroprevalence of canine leishmaniasis in three selected states of Nigeria using indirect enzyme linked immunosorbent assay (ELISA). Two hundred and seventy-three canine sera were tested for Leishnmnia IgG antibodies. Dogs sampled were grouped into young (<1 year) and adult (>1 year). Total prevalence recorded was 4.40 % (12/273). There was no significant difference (P > 0.05) between sera of hunting (4.83 %) and companion dogs (3.03 %). Furthermore, there was no significant difference (P > 0.05) between young and adults dogs. There was no correlation between sex and prevalence of canine leishmaniasis. However, significant difference (P < 0.05) was observed in the prevalence of each state with Kwara, Oyo and Ogun having 14.63, 3.33 and 1.32 % respectively. The result of this study established the presence of canine leishmaniasis in Oyo, Ogun and Kwara Slates of Nigeria making the zoonotic form of the disease a possibility